Analisis Faktor Penghambat Berwirausaha pada Pengrajin Sulaman Wanita di Jorong Lundang Kanagarian Panampuang Kabupaten Agam - Rahmidani, Rose (Jurnal Kajian Manajemen Bisnis, 2014)
The objective of the research is to identify the internal and eksternal factors representing the obstruct of embroidery craftwomen in Jorong Lundang Kanagarian Panampuang. The benefits of this research to improve a literature for woman entrepreneurship. Thus, obtain benefits for local government and cooperative departementÂ  in Jorong Lundang Kanagarian Panampuang to expand small entrepreneurship and create new small medium entrepreneurship. A total 50 sampel complete the questionnaire use Likert Scale were obtained. Confirmatory factors analysis method were used to indicate factors have an impact for embroidery craftwomen to develop their enterprise. The finding confirmed that the most factor that obtrusctÂ  is feminity factors. Further, findings suggest to give information to craftwomen and facilitate them to obtain capital working and cultivating business from creditor both private and government party.